Analisis Risiko Produksi Bunga Anggrek Bulan dan Dendrobium di Raja Bunga Anggrek Kabupaten Semarang - Rinanti Amelia Rizky Santosa; Hery Setiyawan; Dinda Ayu Sekarnurani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Orchids are one of the most widely cultivated ornamental plants in Indonesia. Raja Bunga Anggrek is one of the largest orchid producers with high demand in Semarang Regency. Fluctuating production output indicates a high level of production risk. The objective of this study is to identify the occurrence and sources of risk in orchid cultivation activities and to analyze the priorities for risk management in orchid production activities at Raja Bunga Anggrek in Semarang Regency. The research location was selected purposively, considering that Raja Bunga Anggrek is one of the largest orchid producers in Semarang Regency. The research method employed a case study with a quantitative approach. Key informants were selected using a purposive method, resulting in 6 key informants. This study utilized both primary and secondary data. Primary data were derived from questionnaire-based interviews with respondents and observations, while secondary data were obtained from the company’s annual reports. The analytical methods used in this study were the Coefficient of Variation (CV) and the House of Risk (HOR). The CV value was 6%, indicating that the risk level is classified as moderate. HoR Phase 1 indicates there are 19 events and 8 risk sources. Five risk sources are prioritized and require risk management strategies. The resulting production risk management strategies, in order of priority, are: optimizing plant care (PA1), using alternative raw materials (PA2), performance evaluation (PA6), reducing watering frequency (PA4), post-harvest pruning (PA5), and removing shade nets (PA3) at Raja Bunga Anggrek in Semarang Regency, ranked based on ETD values with the highest and lowest rankings being PA1 and PA3, respectively.Keywords: Orchids, House of Risk, Mitigation, Risk.